What are the effects of COVID-19 on the environment? - Melidis, Michail (HAPSc Policy Briefs Series, 2020)
Contrary to the socio-economic aspects of the coronavirus crisis, the environment has comparably attracted lesser attention. To the question, if there is a silver lining to the global pandemic, existing data and studies show that the environment is an unanticipated beneficiary that gives a glimmer of hope for the post-COVID-19 period. Acknowledging the difficulties in conducting in-depth evaluations over the environmental impacts as the pandemic still unfolds, some preliminary inferences can be drawn. The aim of this paper is to outline and analyse the indirect effects of COVID-19 on the environment for a better understanding and knowledge during the lockdown at the international level. Indicatively, some of the positive effects are met in the decrease of GHG emissions, the fall of fossil fuel consumption, the improved air and water quality, and the re-emergence of wildlife. On the other hand, key challenges lie in the significant increase in medical waste, waste management, and environmental pollution.